Low-Dose Aspirin as Primary Prophylaxis for Cardiovascular Events in Rheumatoid Arthritis: An Italian Multicentre Retrospective Study. (2nd May 2019) - Iacono, Daniela; Fasano, Serena; Pantano, Ilenia; D'Abrosca, Virginia; Ruscitti, Piero; Margiotta, Domenico Paolo Emanuele; Navarini, Luca; Maruotti, Nicola; Grembiale, Rosa Daniela; Cantatore, Francesco Paolo; Afeltra, Antonella; Giacomelli, Roberto; et al.
Abstract : Objective . To investigate the role of acetylsalicylic acid (ASA) in reducing the incidence of cardiovascular (CV) events in an Italian multicentre rheumatoid arthritis (RA) inception cohort. Methods . The clinical charts of RA patients consecutively admitted to 4 Italian centres for their 1 st visit from November 1, 2000, to December 31, 2015, and followed up till December 2016 were retrospectively investigated for the incidence of CV events. Patients were subdivided into two groups, namely, ASA- and non-ASA-treated groups. The Kaplan–Meier curve and log-rank test were used to investigate differences in event-free survival. Cox regression analysis was carried out to identify factors associated with CV event occurrence. Results . Seven hundred forty-six consecutive RA patients were enrolled and followed up for a median of 5.6 years (range 2.9–8.9 years). The incidence rate (IR) of CV events was 8/1000 person-years (p-ys) in the overall cohort. The IR of CV events was significantly lower in the ASA-treated group with respect to the non-ASA-treated group (IR 1.7 vs. 11.8/1000 p-ys;p = 0.0002 ). The CV event-free rate was longer in ASA-treated patients than in non-ASA-treated patients (log-rank test 12.8;p = 0.0003 ). At multivariable analysis, arterial hypertension (HR 9.3) and hypercholesterolemia (HR 2.8) resulted to be positive predictors and ASA (HR 0.09) and hydroxychloroquine (HCQ) (HR 0.22) to be negative predictors. Conclusion . The IR of CV events in our Italian multicentre cohort was lower than that reported in other European and non-European cohorts. Low-dose ASA may have a role in the primary prophylaxis of CV events in RA patients.